O papel dos atores sociais na construção de uma cadeia de fornecimento Waste-to-Energy sob a ótica do empreendedorismo institucional - Corrêa, Adely Ribeiro Meira (2020)
The growing generation of solid urban waste (MSW) causes environmental, social and economic impacts. Efforts must be employed by institutional entrepreneurs capable of solving highly complex problems through technical, political and social skills, multifaceted strategies and the engagement of discursive interventions for change, generating collective action. In this sense, this work aims to analyze the participation of social actors in the construction of a waste-to-energy supply chain (WTE) from the perspective of institutional entrepreneurship. The units of analysis of this study are the social actors involved in the construction of a WTE supply chain at the Municipal Landfill West of Caucaia - ASMOC located in the state of Ceará. This chain was formed through a partnership involving the state government, municipal governments and companies, which designed the installation of the largest plant in the country to convert MSW biogas into the production of renewable natural gas for injection into the distribution network of Gas Company of Ceará. This is a qualitative study carried out through semi-structured interviews with the key actors involved in the construction of the WTE chain. The strategy adopted in this empirical research was the case study. The interview script was used to gather primary data on the initial motivations of the project, the structuring of the WTE chain, the identification of barriers that emerged in the process of change, skills and strategies adopted by social actors in overcoming these barriers. Secondary data were collected from websites and official documents from public and private institutions. The path dependence research technique was adopted for the construction of the historical trajectory and the analysis of the interviews was carried out using the content analysis technique. The results of the research show that institutional entrepreneurs can lead the change as peripheral actors, winning the approval of a new institutional logic by the central actors. The political strength of the state government was also seen as a differential for the success of the WTE chain. Among the strategies identified, the selection of partners based on pre-existing trust relationships proved to be a crucial strategy. This study contributes to the understanding of the role of institutional entrepreneurs in episodes of change in the organizational field.